Kernel Analog Forecasting with Koopman Operator Theory for Indo-Pacific Climate Variability: A Nonlinear Spatio-Temporal Statistical Framework - Dhilshath Shajahan; Ali Akg¨ul (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2026)
Skillful long-range forecasting of the El Niño-Southern Oscillation (ENSO) andthe Indian Ocean Dipole (IOD) remains, despite decades of sustained research effort,an open problem of substantial societal weight.The difficulty is attributable to a basic tension involving the structuralinappropriateness of classical linear statistical frameworks, despite theiranalytical tractability, to regimes whose commencement and termination ofextreme events are nonlinear, with lead times above five months.We describe here a forecasting architecture that fuses Kernel AnalogForecasting (KAF) with the operator-theoretic machinery of Koopmanspectral analysis, thus re-formulating a nonlinear, high-dimensional predictionproblem as linear regression in a reproducing kernel Hilbert space (RKHS).The predictor representation takes the form of an anisotropic, Markov-normalisedGaussian kernel constructed on delay-coordinate embeddings of Indo-Pacific seasurface temperature (SST) fields, with the anisotropy parameter optimised topreferentially weight pairs of states evolving along coherent dynamical directions.Assuming ergodicity and mild regularity, we prove convergence of the KAF estimatorto the Koopman-propagated conditional expectation of the target observable the L^2-optimal predictor (Theorem thm:convergence).Against calibrated multifrequency synthetic signals, KAF sustains patterncorrelation above 0.5 to roughly 14 months ahead, versus 7 months for alinear inverse model baseline; root-mean-square error falls by 18-26%across the full verification horizon.The notorious spring predictability barrier weakens materially, and probabilisticevent forecasts based on Brier Skill Score and the Kullback-Leibler relativeentropy exhibit sharper, less-biased distributions than either the linearor comparators.